Interchangeability of right ventricular longitudinal shortening fraction assessed by transthoracic and transoesophageal echocardiography in the perioperative setting: A prospective study - Beyls, Christophe; Huette, Pierre; Vangreveninge, Paul; Leviel, Florent; Daumin, Camille; Ammar, BenAmmar; Touati, Gilles; Roger, Bouzerar; Caus, Thierry; Dupont, Hervé; Abou-Arab, Osama; Momar, Diouf; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Conventional transthoracic (TTE) and transoesophageal echocardiography (TEE) parameters assessing right ventricle (RV) systolic function are daily used assuming their clinical interchangeability. RV longitudinal shortening fraction (RV-LSF) is a two-dimensional speckle tracking parameter used to assess RV systolic function. RV-LSF is based on tricuspid annular displacement analysis and could be measured with TTE or TEE. Objective: The aim of the study was to determine if RV-LSFTTE and RV-LSFTEE measurements were interchangeable in the perioperative setting. Methods: Prospective perioperative TTE and TEE echocardiography were performed under general anesthesia during scheduled cardiac surgery in 90 patients. RV-LSF was measured by semi-automatic software. Comparisons were performed using Pearson correlation and Bland-Altman plots. RV-LSF clinical agreement was determined as a range of -5% to 5%. Results: Of the 114 patients who met the inclusion criteria, 90 were included. The mean preoperative RV-LSFTTE was 20.4 4.3% and 21.1±4.1% for RV-LSFTEE. The agreement between RV-LSF measurements was excellent, with a bias at -0.61 and limits of agreement of -4.18 to 2.97 %. All measurements fell within the determined clinical agreement interval in the Bland-Altman plot. Linear regression analysis showed a high correlation between RV-LSFTTE and RV-LSFTEE measurement (r=0.9; confidence interval [CI] 95%: [0.87-0.94], p<0.001). Conclusion: RV-LSFTTE and RV-LSFTEE measurements are interchangeable, allowing RV-LSF to be a helpful parameter for assessing perioperative changes in RV systolic function.